Pengenalan Teknologi Digital Berbasis Bencana untuk Mencapai Disaster Resilience bagi Siswa Sekolah Dasar - Ichy Lucya Resta; Husnul Hamdi; Fendriani, Yoza; Fernando Mersa Putra; Maulina Tanjung (Jurnal Tiyasadarma, 2025)
The urgency of introducing disaster-based digital technology to elementary school students is increasing along with the rising frequency and intensity of natural disasters in Indonesia, particularly in Kerinci Regency. The lack of students' understanding about disaster risks and their mitigation could hinder the achievement of disaster resilience at the community level. The activity was conducted at SDN 48/III Sungai Jambu, Kerinci Regency, involving 20 students. The method used was technology-based learning with a participatory approach, engaging students in discussions, simulations, and the use of the application to understand disaster risks in their surrounding environment. Evaluation was carried out using a survey to assess students' satisfaction with the activity and changes in their understanding of disaster-related topics. Survey results showed that most students were satisfied with the activity and found it beneficial in improving their knowledge of disaster mitigation. Additionally, students demonstrated a better understanding of mitigation measures after participating in the activity. The use of digital technology in disaster education proved to be effective in building awareness and disaster preparedness among students. This activity can serve as a model for enhancing disaster education in other schools, especially in disaster-prone areas.